Teachers’ Narrative Accounts of Culturally Responsive Assessment Strategies in Urban Schools - Rostampour, Elham; Gharavand, Kourosh (Assessment and Practice in Educational Sciences, 2024)
This study explores teachers’ narrative accounts of culturally responsive assessment strategies in urban schools, with a focus on understanding the specific practices, challenges, and reflective processes used by educators in Tehran. A qualitative research design was employed, using semi-structured interviews with 29 teachers from diverse urban schools in Tehran. Participants were purposefully selected to represent various subject areas, grade levels, and cultural backgrounds. Interviews were conducted until theoretical saturation was achieved, and each session was audio-recorded and transcribed verbatim. Data were analyzed using inductive thematic analysis, facilitated by NVivo software, to identify recurring themes, subthemes, and concepts reflecting teachers’ approaches to culturally responsive assessment.Teachers reported a wide range of culturally responsive assessment strategies, including integrating students’ cultural backgrounds into assessment design, contextualizing tasks, and valuing linguistic diversity. Inclusive practices such as building trust, reducing bias, and engaging families were commonly cited, along with adaptations for marginalized identities and socioeconomic diversity. Teachers emphasized continuous professional learning, self-assessment, and collaboration despite facing systemic barriers such as standardized testing pressures and limited resources. Narrative accounts illustrated both the promise and challenge of advancing educational equity through assessment in culturally diverse urban settings. The study highlights the complex, multifaceted nature of culturally responsive assessment in urban schools, emphasizing teachers’ commitment to equity, creativity, and ongoing reflection. Effective culturally responsive assessment requires not only individual teacher initiative but also supportive professional communities, flexible policy frameworks, and engagement with families and communities. Systemic changes and targeted professional development are needed to overcome existing barriers and promote sustainable, equitable assessment practices for all students.